Evolutionary diversification and historical biogeography of orchidaceae in Central America: with emphasis on Costa Rica and Panama - Bogarín Chaves, Diego Gerardo (2019)
UCR::Rectoría::Oficina de Asuntos Internacionales y Cooperación Externa (OAICE)